Hubungan Screen Time dengan Pola Tidur Pada Anak Usia Pra Sekolah di TK Budi Karya Surakarta - Siti Nur Solikah; Pris Priyatno (Universitas Malahayati Lampung, 2025)
ABSTRACT The Covid-19 pandemic has impacted the entire world since early 2020, leading to significant changes across various sectors, including education. As a result, all learning activities at every educational level have been conducted online. The Covid-19 pandemic has also changed the habits of children and adults in Indonesia. Children's habits of playing freely with their friends have become more limited because they are confined to the house (social restrictions). Children tend to be actively engaged with gadgets for various activities, including online learning, playing games, and interacting with friends through social media, often without time restrictions each day. The impact of excessive screen time in children causes several problems, one of which is sleep disorders in children. The purpose of this study was to determine the relationship between screen time and sleep patterns in preschool children at Budi Karya Surakarta Kindergarten. This type of research is quantitative research with a descriptive correlative design type with a cross-sectional approach with a sample size of 45 respondents. Sample selection used total sampling, with data analysis using the Chi-Square Test. The results showed that most respondents were in the High Screen Time (HST) category as much as 55% and there were sleep pattern disorders as much as 45%. The results of the study showed that there was a relationship between screen time and sleep patterns in preschool children at Budi Karya Surakarta Kindergarten with a value of (p = 0.000). Keywords: Screen Time, Sleep Patterns, Preschool ABSTRAK Seluruh dunia mengalami pandemi Covid-19 sejak awal tahun 2020. Hal ini menyebabkan terjadinya perubahan di berbagai bidang termasuk bidang pendidikan dimana semua kegiatan pembelajaran dilaksanakan secara online pada semua tingkat pendidikan. Pandemi Covid-19 juga telah merubah kebiasaan kehidupan anak -anak dan orang dewasa di Indonesia. Kebiasaan anak bermain bebas dengan temannya menjadi lebih terbatas karena terkurung di dalam rumah (pembatasan sosial). Anak cenderung aktif dengan aktivitas kegiatan yang ada di dalam gadget seperti pembelajaran online, bermain game, interaksi dengan teman melalui media sosial tanpa batasan waktu setiap hari. Dampak screen time anak yang berlebihan ini menyebabkan beberapa masalah salah satu diantaranya adalah terjadinya gangguan tidur pada anak. Tujuan dari penelitian ini adalah untuk mengetahui hubungan screen time dan pola tidur pada anak usia prasekolah di TK Budi Karya Surakarta. Jenis penelitian ini adalah penelitian kuantitatif dengan jenis rancangan deskriptif korelatif dengan pendekatan cross sectional dengan jumlah sampel 45 responden. Pemilihan sampel menggunakan total sampling, dengan analisa data menggunakan Uji Chi - Square. Hasil penelitian menunjukkan sebagian besar responden dalam kategori High Screen Time (HST) sebanyak 55% dan terjadi gangguan pola tidur sebanyak 45%. Hasil penelitian menunjukkan terdapat hubungan screen time dengan pola tidur pada anak usia prasekolah di TK Budi Karya Surakarta dengan nilai (p = 0.000). Kata Kunci: Screen Tim, Pola Tidur, Pra Sekolah